Design of an Inhalation Chamber and Metrology Assessment to Study Tungsten Aerosol Neurotoxic Effects - Léo Macé; Chrystelle Ibanez; Thomas Gelain; Cécile Bodiot; Laure Juhel; François Gensdarmes (Aerosol and Air Quality Research, 2021)
Abstract To evaluate the neurotoxic effects from exposure to airborne tungsten, we developed a method of generating mass concentrations of this element between 5 and 10 mg m−3, the time-weighted average occupational exposure limits. We then conducted measurements of the aerosol—a challenge due to the high particle density—that enabled us to calculate the deposition in the upper airway and lungs. First, we fed a mixture of coarse tungsten bead powder and aerosolizable tungsten powder, which had been combined in specific mass proportions, to an RBG 1000 (Palas®) equipped with a cyclone at the outlet that filtered out the coarse particles. Then, we simultaneously measured the resultant aerosol, which was generated in an inhalation chamber, using three pairs of instruments—a Dekati® Low Pressure Impactor (DLPI; 30 L min−) and a gravimetric filter holder, a DLPI and a TSI® Aerodynamic Particle Sizer (APS; Model 3321), a TSI Engine Exhaust Particle Sizer (EEPS; Model 3090) and an APS—and symmetrical sampling lines. The mass concentrations obtained with the DLPI and the filter holder were extremely consistent with each other, and the mass median aerodynamic diameters based on the DLPI and the APS data (with the Stokes correction applied to the latter) were also fairly close (1.77 and 1.89 µm, respectively). Additionally, the count median diameter determined from the electrical mobility measured by the EEPS equaled 0.17 µm, which falls beyond both the intended range of the instrument and the range of previously studied aerodynamic sizes. Overall, the results from the DLPI, the APS, and the EEPS showed very good agreement. Computational fluid dynamics (CFD) simulations of the airflows and aerosol dispersion in the inhalation chamber verified that the test aerosol was homogeneous and representative.